The Approaches for Student Affairs Management Development of Nawamintrachinuthit Satriwittaya 2 School Based on The Concept of Student Democratic Way of Life - Tibud, Amornrat; Narintarangkul Na Ayudhaya, Suebsakul (Journal of Humanities and Social Sciences, Rajapruk University, 2021)
The objectives of this research were: 1) to study the current state and desirable state of student affairs management based on the concept of student democratic way of life and 2) to propose approaches for student affairs management of Nawamintrachinuthit Satriwittaya 2 School based on the concept of student democratic way of life. The research informants consisted of 5 administrator, 138 teachers and 347 students. The total 490 informants. The instrument used in this research was a 5 rating scaled questionnaire and evaluation forms of appropriateness and possibility. The statistics used for data analysis were frequency distribution, percentage, mean, standard deviation, and Priority Needs Index. The research revealed that: 1) The current state of student affairs management of Nawamintrachinuthit Satriwittaya 2 School based on the concept of student democratic way of life was at a medium level and the desirable state of student affairs management based on the concept of student democratic way of life was at a high level and the highest need for student affairs management based on the concept of student democratic way of life is student activities, respectively; the top priority was the aspect of wisdom and the last was the aspect of unity. The lowest need for student affairs management based on the concept of student democratic way of life is developing student behavior adjustment, respectively; the top priority was the aspect of unity and the last was the aspect of respect. 2) The approaches for developing student affairs management of Nawamintrachinuthit Satriwittaya 2 School based on the concept of student democratic way of life comprised 2 approaches were 1) the developing student activities to promote the aspect of wisdom and the aspect of respect and 2) the developing student behavior adjustment to promote the aspect of unity and the aspect of wisdom.